Troska o chorych w klasztorach starożytnych w świetle wybranych reguł monastycznych - Kołosowski, Tadeusz (Saeculum Christianum. Pismo Historyczne, 2018)
The purpose of the article is the attempt to answer the question of how Eastern and Western monastic rules normalized the life of those who were ill in ancient monasteries. Did they have among their brothers or sisters some special status? Who were responsible for the sick in the monastery and how hey were responsible for the care of the ill? In this regard, monastic rules are an interesting and unique source of information about activities undertaken to care for ill members of the monastic community. In this regard 7 monastic rules were identified and analyzed. These rules were written in different regions of the contemporary world: Egypt, North Africa, Gaul, Italy and Spain. One was written during IV and VII of century and they concern monks and consecrated women. Each rule deals with the care of the sick those from among the brothers or sisters with a designated role in caring for the sick. These were usually nurses and cellarers. Some rules determined personality traits required. The general supervision over the care of the sick was entrusted to superior of the monastery. Separate rooms or the cells were identified for the sick, sometimes the dining room, the storeroom or the kitchen. All rules seek to ease for the ill requirements concerning of the consumption of meals, fasts, and hygiene needs. They should, if able, perform lighter duties.